Suicidal ideation, attempt and associated factors among adult cancer patients at Jimma University Medical Center, Jimma, Ethiopia, 2023 - Kunno, Kunuya; Belete, Asmare; Anbesaw, Tamrat; Teshome, Monenus; Girma Kassaye, Shimelis; Dawud, Badiru; Birhan, Zelalem (Frontiers in Psychiatry, 2025)
BackgroundCancer has been associated with an increased risk of suicidal behaviors and suicide has been one of the leading causes of non-cancer-related mortality among cancer patients in recent years. However, there is limited evidence on suicidal behaviors in patients diagnosed with cancer at Jimma University Medical Center.ObjectiveThis study aimed to assess the magnitude and associated factors of suicidal ideation and attempts among cancer patients at Jimma University Medical Center, Ethiopia, in 2023.MethodsA hospital-based cross-sectional study was conducted among 271 cancer patients at Jimma University Medical Center from 1 to 30 November 2023. Data were collected using interviewer-administered questionnaires and a consecutive sampling technique was employed. Suicidal ideation and attempts were assessed by the Composite International Diagnostic Interview Module. Logistic regression analysis was used to evaluate the significance of the association between the dependent and independent variables. Variables with a p-value <0.25 were candidates for the multivariable logistic regression so that predictors of suicidal ideation and attempt were identified at a p-value < 0.05, with a 95% confidence interval (CI), in the final model.ResultsThis study reported that 24% and 10.7% of the patients with cancer had suicide ideation and attempted suicide in the previous 12 months, respectively. Being female [adjusted odds ratio (AOR) = 5.35; 95% CI, 2.48–11.54] and having anxiety (AOR = 4.09; 95% CI, 1.85–9.03), psychological distress (AOR = 4.19, 95% CI, 1.61–10.87), and stage IV cancer (AOR = 5.81, 95% CI, 1.73–19.51) were significantly associated with suicidal ideation while having depression [AOR = 3.25, 95% CI, 1.05- 10.06] and anxiety [AOR = 3.50, 95% CI, 1.19-10.32] were significantly associated with attempting suicide.ConclusionNearly one-quarter and one-tenth of the patients with cancer had suicide ideation and attempted suicide in the previous 12 months, respectively. Being female, advanced cancer stage, anxiety, and psychological distress were statistically significantly associated with suicidal ideation. Anxiety and depression were statistically associated with attempting suicide. It is important that oncology professionals routinely perform patient suicidal risk assessment. Consultation services need to be strengthened with psychiatric professionals in cancer treatment centers.